PENGARUH TINGKAT KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN HOTEL MJ SAMARINDA - Eka Yudhyani, Mariana Herwin, H. Eddy Segiarto, (EKONOMIA, 2016)
In this research Issue is the declining level of sales and net profit at PT Timah (Persero) TBk so need to look for causes of the decrease in the level of profitability of the company.The basic theory is the theory of financial management supporting profitability. The hypothesis of this research is "what is the cause of the change of the level of profitability of PT Timah (Persero) TbkTahun 2010-2012".Analysis tool to find out the level of profitability of a company consists of three (3) ratio, i.e. ROE, ROI and NPM.Based on the results of the analysis, the results of calculations of ROE noted that the value of the ROE for the year 2010 amounted to 22,55%, then the value of the ROE in 2011 While 2012 19,51 value of 9,46% ROE. The calculation result based on the results of the analysis of ROI in 2010 known magnitudes of 16,12% ROI with a Net Profit Margin of 14.78%.The year 2011 is known to magnitudes of 13.65% ROI with a Net Profit Margin of 10.26%. The year 2012 is known magnitudes of 7.08% ROI with Net Profit Margin amounted to 5,517, so it can be said that a decline in ROI hypothesis in 2011 through 2012.